14. SOME EXPERIENCES WITH TWO-STAGE ARTHROPLASTY IN PATIENTS WITH JOINT-DESTROYING INFECTION (Vietnam Journal of Community Medicine, 2024)
Purpose: Joint-Destroying Infection (JDI) is a severe stage of Septic Arthritis (SA), due to many causes such as primary joint infection, after joint surgery...The patient eventually becomes disabled because of rapid cartilage destruction due to infection, joint adhesion fusion, loss of function, pain and persistent pus leakage. This is a challenge for orthopedic surgeons. Two-stage arthroplasty has become the gold standard in the surgical treatment of patients with infectious joint destruction. This study, through surgery on 24 patients with joint destruction infections, aims to: - Describe the clinical characteristics and causes of joint destruction leading to the decision to have a 2-stage joint replacement - Evaluate preliminary results, state some initial experiences in surgery for this complex lesion.Materials and methods: Prospective study, 24 cases of joint destruction infection indicated for 2-stage arthroplasty, at Quy Hoa Hospital, conducted from 2017 to 2023. Indications for surgery are based on disease selection, determining the cause of infectious joint destruction according to clinical, X-ray (and MRI), purulent fluid culture, blood biochemical test and cell cultures. Results were evaluated according to Modified Harris Hip Score standards for hip joint, Knee Function Score for knee joint and the improvement infection. The earliest follow-up period is 1 year, the longest is 6 years. Process data according to SPSS 20.0.Result: 24 patients (13 hips and 11 knees) with infected joint destruction underwent 2-stage surgery. The average follow-up time was 32.2 months. After surgery, both clinical and functional outcomes were significantly improved. The overall success rate of the two-stage technique is 87.5%. There were no serious complications or deaths during or after the 2-stage surgery. The most commonly identified pathogen is staphylococcus and most cultures do not grow bacteria. The cause of joint infection is often complications after surgery (osteosynthesis, joint replacement, arthroscopy): 62,5% or corticosteroid injections.Conclude: Two-stage arthroplasty surgery for patients with infected joint destruction is a difficult, heavy surgery that requires patience and is unlikely to be successful. The above results have contributed to proving that this is an effective method to treat irreversible joint destruction due to infection, improve joint function, ultimately improve the patient's quality of life.
Keywords: Two-stage arthroplasty surgery; Joint-Destroying Infection (JDI); Revision - Periprosthetic Joint Infection (PJI); Revision- Aseptic (RA), Septic Arthritis (SA)